Lung ultrasound for respiratory failure in acutely IllpPatients: A Review (2020)
Lung ultrasound (LUS), an imaging modality quickly performed, interpreted, and integrated by the treating physician at the bedside, is a particularly useful tool for acutely ill patients. In evaluating a patient with respiratory failure in the intensive care unit or emergency department, LUS is superior to chest x-ray and generally comparable to computerized tomography, reducing the need for patient transport and radiation exposure. This article will provide a concise review of LUS as it pertains to respiratory failure in general and will include examples of relevant ultrasound images and video clips from critically ill patients.